Recent Developments in Endocrinology of Silkworm, Bombyx mori L. - , Amarnatha N.; , Dukare Pradip Gulabrao; , Bhuvaneshwar Rajesh Naik; , Mamatha N. S.; , Narayanaswamy K. C.; , Manjunath Gowda (Archives of Current Research International, 2024)
Mulberry silkworm has a distinctive role in many of the discoveries which explained the role of the endocrine organs in insect growth and development. Hormones exert specific actions on the growth and development of silkworms, making them advantageous tools for manipulation in sericulture. By precisely controlling hormone levels or applying hormone analogs, sericulturists can conveniently regulate various aspects of silkworm development, such as larval growth, cocoon formation, and pupation. There have been several attempts to utilize hormones, including phytoecdysteroids, JHAs and AJHs, in commercial sericulture to enhance silk production. Phytoecdysteroids, natural compounds found in plants, have been studied for their potential to promote growth and development in silkworms. Similarly, JHAs and AJHs have been explored for their ability to manipulate hormone signaling pathways and influence developmental processes in silkworms.